Correlations between Total Antioxidant Capacity, Polyphenol and Fatty Acid Content of Native Grape Seed and Pomace of Four Different Grape Varieties in Hungary - Éva Szabó; Tamás Marosvölgyi; Gábor Szilágyi; László Kőrösi; János Schmidt; Kristóf Csepregi; László Márk; Ágnes Bóna (Antioxidants, 2021)
Grape pomace is a valuable source of various bioactive compounds such as plant-derived polyphenols and polyunsaturated fatty acids (PUFAs). The commercial demand of grape skin and seed powders as nutraceuticals is still growing. However, no distinction is currently made between unfermented native grape seed and grape seed pomace powders regarding their antioxidant activities. Our aim was to find the relationship between the polyphenol and fatty acid content as well as the antioxidant capacity of native and fermented grape seeds of four different grape varieties harvested in the Villány wine region. According to our results, none of the three investigated polyphenols (resveratrol, rutin, quercetin) could be detected in native grape seed samples in correlation with their significantly lower total antioxidant capacities compared to fermented seed samples. Pinot Noir (PN) grape seed pomace samples with the highest resveratrol and oil content showed significantly higher total antioxidant capacity than Cabernet Sauvignon (CS), Syrah (S) and Blue Portugal (BP) samples. Based on the statistical analysis, positive correlation was found between the fatty acid content and the resveratrol concentration in the pomace samples of different grape varieties. In contrast, rutin concentrations were negatively proportional to the fatty acid content of the fermented samples. No significant correlation was found considering the quercetin content of the samples. According to our findings, grape pomace seems a more promising source in the production of nutraceuticals, since it contains polyphenols in higher concentration and exerts significantly higher antioxidant activity than native grape seeds.